2008
DOI: 10.1524/zkri.2008.1040
|View full text |Cite
|
Sign up to set email alerts
|

Structural complexity in monodisperse systems of isotropic particles

Abstract: Abstract. It has recently been shown that identical, isotropic particles can form complex crystals and quasicrystals. In order to understand the relation between the particle interaction and the structure, which it stabilizes, the phase behavior of a class of two-scale potentials is studied. In two dimensions, the phase diagram features many phases previously observed in experiment and simulation. The three-dimensional system includes the sigma phase with 30 particles per unit cell, not grown in simulations be… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
29
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 32 publications
(41 reference statements)
2
29
0
Order By: Relevance
“…It has been shown that the LJG system forms a glass at r G = 1.4σ and ε = 1.8ε 0 [2] or at r G = 1.47σ and ε = 1.5ε 0 [4][5][6]. We also found that the LJG system cannot be crystallized in the parameter region near these points.…”
Section: Sa020-4mentioning
confidence: 52%
See 2 more Smart Citations
“…It has been shown that the LJG system forms a glass at r G = 1.4σ and ε = 1.8ε 0 [2] or at r G = 1.47σ and ε = 1.5ε 0 [4][5][6]. We also found that the LJG system cannot be crystallized in the parameter region near these points.…”
Section: Sa020-4mentioning
confidence: 52%
“…With the aim of realizing single-component glasses, atoms interacting through the LennardJones-Gauss (LJG) potential [1,2] have been studied by molecular dynamics (MD) simulations in two dimensions [3] and three dimensions, [4][5][6] and it has been shown that the LJG system forms a longlifetime glass when the liquid is cooled. In equilibrium, the system forms crystals and quasi-crystals depending on the parameter region of the LJG potential [1,2].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phase field crystal models have been employed to simulate the growth of 2D QCs [13] and the adsorption properties on a quasicrystalline substrate [14]. The ingredients for 2D quasipattern formation are, first, a propensity towards periodic density modulations with two characteristic wave numbers k 1 and k 2 [15][16][17][18]. The ratio k 2 =k 1 must be close to certain special values; e.g., for dodecagonal QCs the value is 2 cosðπ=12Þ.…”
mentioning
confidence: 99%
“…The session was devoted to the role of electron microscopy in quasicrystal research. Festivities included a conference tour of Jerusalem, where the group photo in Figure 1 was taken, a special Jubilee Dinner, as well as the award of prizes for the best student presentations, sponsored by Journal of Physics D. The second prize was shared by Ruben Ma¨der and Alon Bahabad [19], and the first prize was awarded to Michael Engel [20].…”
mentioning
confidence: 99%